2019
DOI: 10.3390/cancers11040530
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic and Predictive Factors for the Curative Treatment of Esophageal and Gastric Cancer in Randomized Controlled Trials: A Systematic Review and Meta-Analysis

Abstract: Background: An overview of promising prognostic variables and predictive subgroups concerning the curative treatment of esophageal and gastric cancer from randomized controlled trials (RCTs) is lacking. Therefore, we conducted a systematic review and meta-analysis. Methods: PubMed, EMBASE, CENTRAL, and ASCO/ESMO conferences were searched up to March 2019 for RCTs on the curative treatment of esophageal or gastric cancer with data on prognostic and/or predictive factors for overall survival. Prognostic factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 137 publications
1
14
0
Order By: Relevance
“…This result may be because OS is affected by many factors, such as late treatment, other diseases. The multivariate analysis indicated that LVI status, as well as N stage and Clinical-Radscorepredicted LVI status, is an independent prognostic factor in GC patients, which is in accordance with previous results of many studies [11,29,30].…”
Section: Discussionsupporting
confidence: 90%
“…This result may be because OS is affected by many factors, such as late treatment, other diseases. The multivariate analysis indicated that LVI status, as well as N stage and Clinical-Radscorepredicted LVI status, is an independent prognostic factor in GC patients, which is in accordance with previous results of many studies [11,29,30].…”
Section: Discussionsupporting
confidence: 90%
“…Tissue-derived or circulating biomarkers have been widely studied, but these data are hardly applicable to the curative setting at the time being. 11 Starting from that, we searched the literature for articles investigating biomarkers in LAGC and 23 articles were finally included in our review. 1233 The population evaluated in the analysis was homogeneous in terms of clinical setting, since all patients had a gastric or EGJ cancer, received NAC, and underwent radical surgery.…”
Section: Discussionmentioning
confidence: 99%
“…MSI and EBV status have been widely studied, 9,10 but evidence is still heterogeneous and hardly applicable to clinical practice. 11 In addition, the majority of data derived from surgical specimens, often pre-treated with NAC. Ideally, to assess the predictive value of a biomarker to a specific NAC, it should be determined from material obtained before the treatment.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent systematic review and meta-analysis, van den Ende et al identified 23 potentially relevant prognostic and 15 predictive factors for the curative treatment of GC ( 28 ).…”
Section: Prognostic Factors In Gc Histology and Molecular Classificat...mentioning
confidence: 99%